1991
DOI: 10.1089/aid.1991.7.831
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Antibodies to the gp120 V3 Region Principal Neutralizing Determinant of HIV-1MNin Sera from Africa and the Americas

Abstract: Neutralizing antibodies (NA) against HIV-1MN and HIV-1IIIB, and antibodies binding to synthetic peptides (BA) derived from the gp120 envelope V3 region principal neutralizing determinants (PND) of the HIV-1MN, HIV-1IIIB, and HIV-1Z3 virus strains were assayed in HIV-1 antibody-positive sera from the United States, Haiti, Brazil, Zaire, and Zimbabwe. The ability of soluble PND peptide to block neutralization of the corresponding virus by representative sera was also tested. In each country, NA and BA titers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…Infectivity of R2 and MACS strain 9 for HOS CCR5 ϩ cells that did not express CD4 was increased significantly in each of three experiments by the presence of the 313-4 PM mutation. There was some evidence of infectivity of the MACS strain 3 (313-4HI/PM) clone for HOS CCR5 Peptide blocking studies were carried out to evaluate the possibility that anti-V3 antibodies might contribute to the cross-reactivity of HNS2 (6,46). In preliminary studies it was found that addition of peptide to nonimmune serum did not cause the serum to enhance infectivity of virus pseudotyped with R2 envelope (not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infectivity of R2 and MACS strain 9 for HOS CCR5 ϩ cells that did not express CD4 was increased significantly in each of three experiments by the presence of the 313-4 PM mutation. There was some evidence of infectivity of the MACS strain 3 (313-4HI/PM) clone for HOS CCR5 Peptide blocking studies were carried out to evaluate the possibility that anti-V3 antibodies might contribute to the cross-reactivity of HNS2 (6,46). In preliminary studies it was found that addition of peptide to nonimmune serum did not cause the serum to enhance infectivity of virus pseudotyped with R2 envelope (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In one case the peptide was cyclized before lyophilization, as described below. Preparation of a linear MN strain V3 peptide has been described previously (6). Cyclized MN strain 35-mer peptide was obtained from the ARRRP (catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…Seventeen of the 25 convergent peptides include regions that have been described previously as being immunodominant, the V3, Kennedy, Wang, and Gnann epitopes (14,20,27,50,53). Particularly notable was the range of reactivity to the V3 loop, a principal neutralizing and tropism-determining domain (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Also, the V3 loop is the major target for neutralizing [3,4] and enhancing [5][6][7] antibodies, which are part of the immunodominant antibody response in natural and experimental HIV-1 infection [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%